Parental experiences of their child's vulvovaginitis: a qualitative interview study. Issue 6 (December 2019) - McKenna, J.; Bray, L.; Doyle, S.
Summary: Introduction: Vulvovaginitis is described as a common self-limiting paediatric gynaecological condition. Parents' experiences of their child being diagnosed with this condition and subsequent treatment have not previously been described. Aim: The aim of this study was to explore parents' experiences of their child's diagnosis and management of vulvovaginitis. Study design: The study was conducted in the north west of England over a two-year period. Qualitative data were generated by semistructured in-depth interviews. Mothers of nine children with vulvovaginitis consented to participate. Data were analysed using thematic analysis. Results: The analysis of the data resulted in four themes: trauma and uncertainty of initial symptoms, seeking a diagnosis; an uncertain journey, managing the symptoms; a process of trial and error and managing the impact; keeping it private. Parents experienced a difficult and protracted journey to their child's diagnosis and were involved in a process of trial and error to try and monitor and manage what can be a difficult ongoing condition. Discussion: Clinical reports suggest that vulvovaginitis is a minor childhood condition; this is not necessarily the perceptions and experiences of parents, who can experience uncertainty and ongoing difficulty after their child's diagnosis. Conclusion: The diagnosis of vulvovaginitis can have a major and ongoing impact on children's and their family's lives.